2016
DOI: 10.5271/sjweh.3582
|View full text |Cite
|
Sign up to set email alerts
|

Organizational justice and disability pension from all-causes, depression and musculoskeletal diseases: A Finnish cohort study of public sector employees

Abstract: Supervisors` fair treatment of employees and fair decision-making in the organizations are associated with a decreased risk of disability pensioning from all-causes, depression and musculoskeletal diseases. These associations may be attributable to a wider range of favorable work characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 42 publications
3
33
0
Order By: Relevance
“…One possible explanation might be that the group was rather small (n = 170); thus power problems might at least partially explain the null-finding. Also, it is possible that justice perceptions influenced health already prior to the study, so that respondents had habituated to the situation, and that stable low justice was not related to a further decline in health [19,38]. Indeed, analyses based on the full sample including those with prior prescription of antidepressants revealed an increased hazard also for participants experiencing stable low justice as well as increasing justice, suggesting that health problems and possibly low justice perceptions may have been present before inclusion in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation might be that the group was rather small (n = 170); thus power problems might at least partially explain the null-finding. Also, it is possible that justice perceptions influenced health already prior to the study, so that respondents had habituated to the situation, and that stable low justice was not related to a further decline in health [19,38]. Indeed, analyses based on the full sample including those with prior prescription of antidepressants revealed an increased hazard also for participants experiencing stable low justice as well as increasing justice, suggesting that health problems and possibly low justice perceptions may have been present before inclusion in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Yet another recent study from Eib et al (2018) reported significant lagged effects from procedural justice to Notes: Reference group is group 4 (stable high) *Models 2a and 2b are adjusted for sex, age, education, socioeconomic position, marital status, insecure employment in 2010 (estimates not shown, sex and insecure employment remained significant)°M odel 1b and 2b are adjusted for all covariates as above, and also includes events from individuals in receipt of prescribed antidepressant medication in the 2 years up to 2012 depressive symptoms [19]. However, while some have used non-subjective measures of depression, mostly defined as registry-based sickness absence [41] or disability pension [38] due to diagnosed mental disorder, many of the studies looking at organizational justice and health outcomes are exposed to the risk of common method variance. By using medication registers for the outcome, the present study avoided that risk.…”
Section: Discussionmentioning
confidence: 99%
“…Third, in a Finnish cohort study on public employees, relational and procedural justice were associated with reduced risk of disability pension due to depression. However, after adjusting for the effects of effort-reward imbalance and demand-control, effects lost their statistical significance (43). Finally, a Danish prospective study assessed aggregated work-unit data of procedural and relational injustice at work, related to onset of new depression over a 2-year period (44).…”
Section: The Organizational Injustice Modelmentioning
confidence: 99%
“…Most studies focus on the health-related conditions that are linked to SCC, such as depression (47) or stress-related symptoms (burnout/exhaustion) (28). Obviously, these conditions are related to permanent WD (48,49).…”
Section: Similarities and Differences To Previous Studiesmentioning
confidence: 99%